A nationwide population‐based study of social demographic factors, associated diseases and mortality of keratoconus patients in Denmark from 1977 to 2015. Issue 5 (13th November 2018) - Bak‐Nielsen, Sashia; Ramlau‐Hansen, Cecilia H.; Ivarsen, Anders; Plana‐Ripoll, Oleguer; Hjortdal, Jesper
Abstract: Purpose: To study sociodemographic factors, associated diseases and survival of Danish keratoconus patients. Methods: All patients diagnosed with keratoconus 1977–2015 ( n = 2679) were matched to 10 persons who had not been diagnosed with keratoconus ( n = 26 790). Conditional logistic regression assessed whether sociodemographic factors and specific systemic diseases were associated with the odds of keratoconus. Mortality was assessed with time‐to‐event analysis. Results: After adjustment, non‐Europeans had more than threefold higher odds of keratoconus compared to Europeans (OR, 3.34; 96% CI 2.94–3.80). Single persons had 27% higher odds (OR, 1.27; 95% CI 1.13–1.43), and divorced persons had 18% lower odds (OR 0.82; 95% CI 0.68–0.97) of keratoconus compared with persons in a relationship. Persons living in cities with <500 and 500–4999 inhabitants had 40% (OR, 0.60; 95% CI 0.51–0.71) and 30% (OR, 0.70; 95% CI 0.61–0.81) lower odds of keratoconus, respectively, compared with those living in the capital (>1 000 000 inhabitants). Persons receiving government substitution had 68% higher odds of keratoconus (OR, 1.68; 95% CI 1.30–2.17) compared to self‐employed. Keratoconus patients had more than twofold higher odds of asthma (OR, 2.21; 95% CI 1.91–2.55), more than threefold higher odds of allergic rhinitis (OR, 3.44; 95% CI 2.75–4.30), more than sevenfold higher odds of atopic dermatitis (OR, 7.97; 95% CI, 6.21–10.21) and 69% higher odds of depression (OR, 1.69; 95% CI 1.18–2.43). Mortality rates were similar among keratoconus patients and controls (HR, 1.02; 95% CI 0.90–1.16). Conclusion: Danish keratoconus patients differ from controls on several sociodemographic factors and have higher risk of allergic rhinitis, asthma, atopic dermatitis and depression. They do not have excess mortality compared to controls.